Pengaruh Total Assets Dan Total Assets Turnover Terhadap Rating Sukuk Dengan Return On Assets Sebagai Variabel Intervening Studi Pada Sukuk Korporasi Di Indonesia Tahun 2016-2018 - Andika Taftiyanur Rofi (University of Darussalam Gontor, 2020)
Sukuk Rating is a standard that reflects the ability of Sukuk issuers and their willingness to pay principal payments according to schedule. This study aims to determine the effect of Total Assets and Total Assets Turnover on Sukuk Ratings with Return on Assets as Intervening Variables. The population of this study is all corporate Sukuk that circulated in Indonesia from 2016 to 2018. The sampling technique used was purposive sampling techniques, with a sample of 33 corporate Sukuk in Indonesia. This research uses the Partial Leats Square (PLS) approach.The results of this study prove that Total Assets have a significant negative effect on Return on Assets. Meanwhile, Total Assets Turnover has a significant positive effect on Return on Assets. Total Assets and Return on Assets partially have a significant positive effect on Sukuk rating. Meanwhile, Total Assets Turnover has no significant negative effect on Sukuk rating. The Return on Assets variable is considered capable of being an intervening variable for the effect of Total Assets and Total Assets Turnover on Sukuk ratings. Although Return on Assets shows an inconsistent mediation effect, the Return on Assets variable also shows a perfect mediating effect for the effect of Total Assets Turnover on Sukuk rating by changing the insignificant effect into a significant effect